Multi-modal and multi-route transportation problem for hazardous materials under uncertainty. Issue 12 (2nd December 2021) - Xie, Li; Cao, Chengxuan
ABSTRACT: In this article, the multi-modal and multi-route transportation problem for hazardous materials under uncertainty is studied, and an interval 0–1 integer programming model is proposed to optimize the transportation risks and transportation costs during the transportation of hazardous materials. Factors such as freight rates and loading and unloading costs are different when the transportation modes, transportation time and transportation areas are different. Therefore, some parameters in the model are assumed as interval numbers. The proposed model is transformed to a deterministic model by the interval ranking method. In addition, a genetic algorithm is proposed to solve the model. Finally, a real-world case of the multi-modal and multi-route transportation problem for hazardous materials under uncertainty is studied to demonstrate the rationality and effectiveness of proposed model and algorithm.